Formation of Au-Silane Bonds. (27th June 2012) - Yochelis, Shira; Katzir, Eran; Kalcheim, Yoav; Gutkin, Vitaly; Millo, Oded; Paltiel, Yossi
Abstract : Many intriguing aspects of molecular electronics are attributed to organic-inorganic interactions, yet charge transfer through such junctions still requires fundamental study. Recently, there is a growing interest in anchoring groups, which considered dominating the charge transport. With this respect, we choose to investigate self-assembly of disilane molecules sandwiched between gold surface and gold nanoparticles. These assemblies are found to exhibit covalent bonds not only between the anchoring Si groups and the gold surfaces but also in plane crosslinks that increase the monolayer stability. Finally, using scanning tunneling spectroscopy we demonstrate that the disilane molecules provide strong electrical coupling between the Au nanoparticles and a superconductor substrate.